Spatial analysis of hydraulic properties of residual soil slope using a mini disk infiltrometer - Muhammad Mustaqim Bin Mohd Rafik (Nanyang Technological University, 2022)
This project investigates the spatial variability of hydraulic conductivity of residual soil slopes in NTU. The scope of the project involves conducting the mini disk infiltrometer test at several locations on residual soil slopes of the NTU campus. The infiltrometer test will derive the hydraulic properties of the soil sample in terms of hydraulic conductivity according to the cumulative rate of infiltration. To determine its soil properties and grain size distribution, soil samples collected from the sites and will be tested for grain size distribution using the dry and wet sieving methods. The finer soil from the soil samples will be then tested using the hydrometer test for a more accurate grain size analysis of the fines content. The soil samples can then be classified according to the USDA soil texture classification. In the end, I discussed the numerical average of hydraulic conductivity of the soil samples obtained and illustrate the geospatial relationship with the hydraulic properties.